Insights into congenital stationary night blindness based on the structure of G90D rhodopsin - Singhal, Ankita (European Molecular Biology Organization, 2013)
We present active-state structures of the G protein-coupled receptor (GPCRs) rhodopsin carrying the disease-causing mutation G90D. Mutations of G90 cause either retinitis pigmentosa (RP) or congenital stationary night blindness (CSNB), a milder, non-progressive form of RP. Our analysis shows that the CSNB-causing G90D mutation introduces a salt bridge with K296. The mutant thus interferes with the E113Q-K296 activation switch and the covalent binding of the inverse agonist 11-cis-retinal, two interactions that are crucial for the deactivation of rhodopsin. Other mutations, including G90V causing RP, cannot promote similar interactions. We discuss our findings in context of a model in which CSNB is caused by constitutive activation of the visual signalling cascade.